Isotopic insights into the fate of atmospheric nitrogen in alpine tundra ponds with contrasting land cover and cryospheric conditions - R. Balestrini; N. Colombo; M. Freppaz; M.F. Lehmann; C. Delconte; E. Pintaldi; F. Salerno; I. Matiatos (CATENA, 2026)

Using La2O3/Printex carbon cathode for simultaneous H2O2 generation and synergistic amitriptyline degradation in aqueous matrices - F. Escalona-Durán; C.H.M. Fernandes; G.O.S. Santos; R.J.A. Felisardo; W.R.P. Barros; R. Colombo; M.A. R. Rodrigo; M.R.V. Lanza (Process Safety and Environmental Protection, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

P18-36 “Cross-species” Liver Microtissues: Species-specific microphysiological test systems for comparative toxicological in vitro studies during nonclinical drug safety assessment - M.V. Colombo; F. Wenz; L. Fäs; A. Pawlowska; A. Wolf; B.G. Filippi (Toxicology Letters, 2025)

In-situ electrogeneration of H2O2 and hydroxyl radical applied for venlafaxine degradation: A novel strategy using FeSe2-modified carbon gas diffusion electrode - Fausto E. Bimbi Júnior; Oswaldo C. Junior; Robson S. Souto; João Pedro P. Encide; Micael M. Baruch; Maria C.V. Felipe; Larissa Fernandes; Isabela F. Araujo; Carlos H.M. Fernandes; Igor G.S. Oliveira; Kathia M. Honorio; Renata Colombo; et al. (Chemical Engineering Journal, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Telescopic alluvial fans and pleistocene-holocene temporary lakes in the quebradas del Río Toro and Tastil (Salta, NW Argentina): main sedimentary features - F. Colombo; J. A. Salfity; M. C. Sánchez (Journal of Iberian Geology, 2025)
The Toro and Tastil Quebradas (river valleys) present different terrace-like geoforms made up of deposits of coarse-grained clastic materials. These terraces display convex-upward surfaces, a highly variable distribution, have a small lateral extension and depend on the lithology of the geological basement, which differs significantly along the quebradas . The number of terraces between one area and another indicates that these terraced geoforms should not be ascribed to one single cause, but rather to a variety of factors, i.e. local variations at base-level. The coarse-grained materials of the terraces are usually arranged in roughly horizontal layers that characterize the outcrops. These are interfingered with fine-grained mud-rich materials. The freshwater gastropod remains in the mud-rich materials indicate that they accumulated in lacustrine-like sedimentary environments. These developed from alluvial fans that spread out from the lateral quebradas to occupy the entire main valley (q uebrada) , giving rise to natural dams and temporary lakes upstream. Absolute data obtained by radiocarbon ( 14 C) methods strongly suggest that the alluvial fans were coeval with the temporary lakes in the Upper Pleistocene - Middle Holocene. The El Niño Southern Oscillation (ENSO) effects could have brought about the local variations in base-level that generated the younger temporary lakes, whereas the older ones were probably controlled by precession cycles (at about 21,000 y). The large number of temporary lakes scattered across the region suggests the overlapping of forcing factors at local and regional scales.

P12-05 Species-specific liver microtissues: a set of micro-physiological systems to study translational hepatotoxicity in safety assessment - M.V. Colombo; F. Wenz; L. Fäs; A. Borgström; A. Wolf; B.G.H. Filippi (Toxicology Letters, 2024)

An aquaculture risk model to understand the causes and consequences of Atlantic Salmon mass mortality events: A review - Zaman Sajid; A. Kurt Gamperl; Christopher C. Parrish; Stefanie M. Colombo; Javier Santander; Charles Mather; Barbara Neis; Ingunn Marie Holmen; Ramón Filgueira; Cynthia H. McKenzie; Lissandra Souto Cavalli; Mohamed Jeebhay; et al. (Reviews in Aquaculture, 2024)
Mass mortality events (MMEs) are defined as the death of large numbers of fish over a short period of time. These events can result in catastrophic losses to the Atlantic salmon aquaculture industry and the local economy. However, they are challenging to understand because of their relative infrequency and the high number of potential factors involved. As a result, the causes and consequences of MMEs in Atlantic salmon aquaculture are not well understood. In this study, we developed a structural network of causal risk factors for MMEs for aquaculture and the communities that depend on Atlantic salmon aquaculture. Using the Interpretive Structural Modeling (ISM) technique, we analysed the causes of Atlantic salmon mass mortalities due to environmental (abiotic), biological (biotic) and nutritional risk factors. The consequences of MMEs were also assessed for the occupational health and safety of aquaculture workers and their implications for the livelihoods of local communities. This structural network deepens our understanding of MMEs and points to management actions and interventions that can help mitigate mass mortalities. MMEs are typically not the result of a single risk factor but are caused by the systematic interaction of risk factors related to the environment, fish diseases, feeding/nutrition and cage‐site management. Results also indicate that considerations of health and safety risk, through pre‐ and post‐event risk assessments, may help to minimize workplace injuries and eliminate potential risks of human fatalities. Company and government‐assisted socio‐economic measures could help mitigate post‐mass mortality impacts. Appropriate and timely management actions may help reduce MMEs at Atlantic salmon cage sites and minimize the physical and social vulnerabilities of workers and local communities.

Towards a standardized, ground-based network of hyperspectral measurements: Combining time series from autonomous field spectrometers with Sentinel-2 - Paul Naethe; Andrea De Sanctis; Andreas Burkart; Petya K.E. Campbell; Roberto Colombo; Biagio Di Mauro; Alexander Damm; Tarek El-Madany; Francesco Fava; John A. Gamon; Karl F. Huemmrich; Mirco Migliavacca; et al. (Remote Sensing of Environment, 2024)

Reappraisal of red clays in porcelain stoneware production: Compositional and technological characterization - Riccardo Fantini; Sonia Conte; Alessandro F. Gualtieri; Michele Dondi; Francesco Colombo; Mattia Sisti; Chiara Molinari; Chiara Zanelli; Rossella Arletti (Applied Clay Science, 2024)

High-resolution temporal variations of nitrate in a high-elevation pond in alpine tundra (NW Italian Alps) - N. Colombo; R. Balestrini; D. Godone; D. Vione; D. Said-Pullicino; G. Viviano; M. Martin; C.A. Delconte; S. Fratianni; A.G. Capodaglio; E. Pintaldi; M. Freppaz; et al. (CATENA, 2024)

Microstructure of Deposited AISI M4 High Speed Steel On AISI D2 Tool Steel Substrate Using L-DED Process - Giovanna F. Colombo; Moysés L. de Lima; Mário Boccalini; Alzira V. O. Corrêa; Marcelo T. Veiga (BHM Berg- und Hüttenmännische Monatshefte, 2024)

Calorimetric determination of wet snow liquid water content: The effect of test conditions on the calorimeter constant and its impact on the measurement uncertainty - D. Fasani; F. Cernuschi; L.P.M. Colombo (Cold Regions Science and Technology, 2023)

Psilocybin prevents reinstatement of alcohol seeking by disrupting the reconsolidation of alcohol-related memories - F. Benvenuti; D. Colombo; L. Soverchia; N. Cannella; E. Domi; R. Ciccocioppo (Psychopharmacology, 2023)

Study of the mechanical properties of thermoplastic polyurethane (TPU) recycled from end-of-life ski-boots and techno-economic analysis (TEA) of the mechanical recycling processes - A. Nanni; L. Crosetta; G. La Fauci; F. Biagi; M. Parisi; D. Colombo; M. Colonna (Sustainable Chemistry and Pharmacy, 2023)

Hydrological, thermal and chemical influence of an intact rock glacier discharge on mountain stream water - F. Bearzot; N. Colombo; E. Cremonese; U. Morra di Cella; E. Drigo; M. Caschetto; S. Basiricò; G.B. Crosta; P. Frattini; M. Freppaz; P. Pogliotti; F. Salerno; et al. (Science of The Total Environment, 2023)

Colostrum quality associations with passive immunity transfer in foals - H B Magalhães; G Araujo; I Colombo; K M Spencer; G Podico; I F Canisso (Journal of Equine Veterinary Science, 2023)

: A high-order discontinuous Galerkin solver for flow simulations and multi-physics applications - E. Ferrer; G. Rubio; G. Ntoukas; W. Laskowski; O.A. Mariño; S. Colombo; A. Mateo-Gabín; H. Marbona; F. Manrique de Lara; D. Huergo; J. Manzanero; A.M. Rueda-Ramírez; et al. (Computer Physics Communications, 2023)

Invasive Aspergillosis in Patients with Acute Leukemia: Comparison Between Acute Myeloid and Acute Lymphoid Leukemia - Arnaldo L. Colombo; Maria Daniela Bergamasco; Simone A. Nouér; Paulo de Tarso Oliveira e Castro; Alessandro C. Pasqualotto; Flavio de Queiroz-Telles; Edson Abdala; Jessica F. Ramos; Diego R. Falci; Marcio Nucci (Mycopathologia, 2023)

Correction to: The thyroid status reprograms T cell lymphoma growth and modulates immune cell frequencies - H. A. Sterle; M. L. Barreiro Arcos; E. Valli; M. A. Paulazo; S. P. Méndez Huergo; A. G. Blidner; F. Cayrol; M. C. Díaz Flaqué; A. J. Klecha; V. A. Medina; L. Colombo; G. A. Rabinovich; et al. (Journal of Molecular Medicine, 2023)

Disjunct resident population of Melodious Lark Mirafra cheniana discovered in East Africa - Brian W. Finch; R. Stratton Hatfield; Silvia Colombo; Adam S. Kennedy; Marije te Raa; Martin Irestedt; Dawid H. de Swardt; Joe Grosel; Derek Engelbrecht; Callan Cohen; Urban Olsson; Paul F. Donald; et al. (Journal of Ornithology, 2023)
We describe the discovery of a previously unknown population of Melodious Lark Mirafra cheniana from northern Tanzania and southern Kenya, some 2000 km north of what was previously thought to be its northern limit in central Zimbabwe. The identification of this population as M. cheniana is based primarily on analyses of mitochondrial DNA and song. We also clarify relationships within this genus by sequencing material of White-tailed Lark Mirafra albicauda for the first time; although its relationships with other species in the group remain unclear, our analyses clearly show it to be different from M. cheniana in the newly discovered population. The discovery of a population of M. cheniana in East Africa conforms to a known pattern for closely related lark species to have disjunct distributions in southern and eastern Africa.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Exposure to 17β estradiol causes erosion of sexual dimorphism in Bluegill (Lepomis macrochirus) - Neeta Parajulee Karki; Robert E. Colombo; Karen F. Gaines; Anabela Maia (Environmental Science and Pollution Research, 2021)

Gulliver’s virtual travels: active embodiment in extreme body sizes for modulating our body representations - S. Serino; F. Scarpina; A. Chirico; A. Dakanalis; D. Di Lernia; D. Colombo; V. Catallo; E. Pedroli; G. Riva (Cognitive Processing, 2020)
It is noted that the perceptual experience of body and space can be modulated by changing the action capabilities or by manipulating the perceived body dimensions through a multisensory stimulation. This study adds to pre-existing literature by investigating the alterations in bodily experience following embodiment to both enlarged and shrunked bodies, while participants actively navigated in a virtual environment. A normal-sized body served as a reference condition. After each embodied navigation, participants estimated the height and width of three different body parts. Results revealed that the embodiment over shrunked body induced a significant reduction in participants’ body image, while no changes were reported after the embodiment over the enlarged body. Findings were discussed in terms of previous literature exploring the constraints implicated in the ownership over different bodies.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Reduction of hippocampal IL-6 levels in LPS-injected rats following acute exendin-4 treatment - Luiza P. Géa; Eduarda D. da Rosa; Bruna S. Panizzutti; Érica Z. de Aguiar; Larissa F. de Oliveira; Pamela Ferrari; Angelo Piato; Rosane Gomez; Rafael Colombo; Adriane R. Rosa (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Projected declines in global DHA availability for human consumption as a result of global warming - Stefanie M. Colombo; Timothy F. M. Rodgers; Miriam L. Diamond; Richard P. Bazinet; Michael T. Arts (Ambio, 2020)
Docosahexaenoic acid (DHA) is an essential, omega-3, long-chain polyunsaturated fatty acid that is a key component of cell membranes and plays a vital role in vertebrate brain function. The capacity to synthesize DHA is limited in mammals, despite its critical role in neurological development and health. For humans, DHA is most commonly obtained by eating fish. Global warming is predicted to reduce the de novo synthesis of DHA by algae, at the base of aquatic food chains, and which is expected to reduce DHA transferred to fish. We estimated the global quantity of DHA (total and per capita) currently available from commercial (wild caught and aquaculture) and recreational fisheries. The potential decrease in the amount of DHA available from fish for human consumption was modeled using the predicted effect of established global warming scenarios on algal DHA production and ensuing transfer to fish. We conclude that an increase in water temperature could result, depending on the climate scenario and location, in a ~ 10 to 58% loss of globally available DHA by 2100, potentially limiting the availability of this critical nutrient to humans. Inland waters show the greatest potential for climate-warming-induced decreases in DHA available for human consumption. The projected decrease in DHA availability as a result of global warming would disproportionately affect vulnerable populations (e.g., fetuses, infants), especially in inland Africa (due to low reported per capita DHA availability). We estimated, in the worst-case scenario, that DHA availability could decline to levels where 96% of the global population may not have access to sufficient DHA.

New Molecular Markers Distinguishing Fonsecaea Agents of Chromoblastomycosis - Gabriela X. Schneider; Renata R. Gomes; Amanda Bombassaro; Kassiely Zamarchi; Morgana F. Voidaleski; Flávia F. Costa; Aniele C. R. Leão; Bruna J. F. S. Lima; Bruna S. Soley; Israella R. Colombo; Giovanna Z. Cândido; Mohammad J. Najafzadeh; et al. (Mycopathologia, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Pumice clasts in cross stratified basalt-dominated sandstones and conglomerates. Characteristics and depositional significance: Huarenchenque Fm (Neuquén, Argentina) - F. Colombo; R. Bargalló; L. A. Spalletti; P. Enrique; I. Queralt (Journal of Iberian Geology, 2019)

The calcium-binding type III repeats domain of thrombospondin-2 binds to fibroblast growth factor 2 (FGF2) - Marco Rusnati; Patrizia Borsotti; Elisabetta Moroni; Chiara Foglieni; Paola Chiodelli; Laura Carminati; Denise Pinessi; Douglas S. Annis; Giulia Paiardi; Antonella Bugatti; Alessandro Gori; Renato Longhi; et al. (Angiogenesis, 2019)

In Situ Tissue Labeling of Cerebral Amyloid Using HIV-Related Tat Peptide - E. Maderna; L. Colombo; A. Cagnotto; G. Di Fede; A. Indaco; F. Tagliavini; M. Salmona; G. Giaccone (Molecular Neurobiology, 2018)

Classifying zones of suitability for manual drilling using textural and hydraulic parameters of shallow aquifers: a case study in northwestern Senegal - F. Fabio Fussi; Letizia Fumagalli; Francesco Fava; Biagio Di Mauro; Cheik Hamidou Kane; Magatte Niang; Souleye Wade; Barry Hamidou; Roberto Colombo; Tullia Bonomi (Hydrogeology Journal, 2017)

The thyroid status reprograms T cell lymphoma growth and modulates immune cell frequencies - H. A. Sterle; M. L. Barreiro Arcos; E. Valli; M. A. Paulazo; S. P. Méndez Huergo; A. G. Blidner; F. Cayrol; M. C. Díaz Flaqué; A. J. Klecha; V. A. Medina; L. Colombo; G. A. Rabinovich; et al. (Journal of Molecular Medicine, 2016)

Sun‐induced fluorescence – a new probe of photosynthesis: First maps from the imaging spectrometer HyPlant - U. Rascher; L. Alonso; A. Burkart; C. Cilia; S. Cogliati; R. Colombo; A. Damm; M. Drusch; L. Guanter; J. Hanus; T. Hyvärinen; T. Julitta; et al. (Global Change Biology, 2015)
Variations in photosynthesis still cause substantial uncertainties in predicting photosynthetic CO 2 uptake rates and monitoring plant stress. Changes in actual photosynthesis that are not related to greenness of vegetation are difficult to measure by reflectance based optical remote sensing techniques. Several activities are underway to evaluate the sun‐induced fluorescence signal on the ground and on a coarse spatial scale using space‐borne imaging spectrometers. Intermediate‐scale observations using airborne‐based imaging spectroscopy, which are critical to bridge the existing gap between small‐scale field studies and global observations, are still insufficient. Here we present the first validated maps of sun‐induced fluorescence in that critical, intermediate spatial resolution, employing the novel airborne imaging spectrometer HyPlant . HyPlant has an unprecedented spectral resolution, which allows for the first time quantifying sun‐induced fluorescence fluxes in physical units according to the Fraunhofer Line Depth Principle that exploits solar and atmospheric absorption bands. Maps of sun‐induced fluorescence show a large spatial variability between different vegetation types, which complement classical remote sensing approaches. Different crop types largely differ in emitting fluorescence that additionally changes within the seasonal cycle and thus may be related to the seasonal activation and deactivation of the photosynthetic machinery. We argue that sun‐induced fluorescence emission is related to two processes: (i) the total absorbed radiation by photosynthetically active chlorophyll; and (ii) the functional status of actual photosynthesis and vegetation stress.

Continuous streamflow simulation for index flood estimation in an Alpine basin of northern Italy - G. Ravazzani; D. Bocchiola; B. Groppelli; A. Soncini; M.C. Rulli; F. Colombo; M. Mancini; R. Rosso (Hydrological Sciences Journal, 2015)

Direct numerical simulation of fully saturated flow in natural porous media at the pore scale: a comparison of three computational systems - M. Siena; J. D. Hyman; M. Riva; A. Guadagnini; C. L. Winter; P. K. Smolarkiewicz; P. Gouze; S. Sadhukhan; F. Inzoli; G. Guédon; E. Colombo (Computational Geosciences, 2015)

AtAPOSTART1, an Arabidopsis thaliana PH-START domain protein involved in seed germination - F. Resentini; S. Vanzulli; G. Marconi; L. Colombo; E. Albertini; S. Masiero (Plant Biosystems, 2014)

B25716/1: a novel albumin-binding Gd-AAZTA MRI contrast agent with improved properties in tumor imaging - E. Gianolio; C. Cabella; S. Colombo Serra; G. Valbusa; F. Arena; A. Maiocchi; L. Miragoli; F. Tedoldi; F. Uggeri; M. Visigalli; P. Bardini; S. Aime (JBIC Journal of Biological Inorganic Chemistry, 2014)

Apple ( Malus domestica L. Borkh) as an emerging model for fruit development - G. Eccher; S. Ferrero; F. Populin; L. Colombo; A. Botton (Plant Biosystems, 2014)

The relationship between carbonate facies, volcanic rocks and plant remains in a late Palaeozoic lacustrine system (San Ignacio Fm, Frontal Cordillera, San Juan province, Argentina) - P. Busquets; I. Méndez-Bedia; G. Gallastegui; F. Colombo; R. Cardó; O. Limarino; N. Heredia; S. N. Césari (International Journal of Earth Sciences, 2013)

Heme oxygenase 1 (HO-1) challenges the angiogenic switch in prostate cancer - M. Ferrando; G. Gueron; B. Elguero; J. Giudice; A. Salles; F. Coluccio Leskow; E. A. Jares-Erijman; L. Colombo; R. Meiss; N. Navone; A. De Siervi; E. Vazquez (Angiogenesis, 2011)

Calcification in bleached and unbleached Montastraea faveolata: evaluating the role of oxygen and glycerol - M. F. Colombo-Pallotta; A. Rodríguez-Román; R. Iglesias-Prieto (Coral Reefs, 2010)

With time on our side? Task-dependent compensatory processes in graceful aging - M. Berlingeri; G. Bottini; L. Danelli; F. Ferri; D. Traficante; L. Sacheli; N. Colombo; M. Sberna; R. Sterzi; G. Scialfa; E. Paulesu (Experimental Brain Research, 2010)

Ecological portrayal of old‐growth forests and persistent woodlands in the Cilento and Vallo di Diano National Park (southern Italy) - M. Marchetti; R. Tognetti; F. Lombardi; U. Chiavetta; G. Palumbo; M. Sellitto; C. Colombo; P. Iovieno; A. Alfani; D. Baldantoni; A. Barbati; B. Ferrari; et al. (Plant Biosystems, 2010)

3-D distribution of nongeniculate corallinales: a case study from a reef crest of South Sinai (Red Sea, Egypt) - A. Caragnano; F. Colombo; G. Rodondi; D. Basso (Coral Reefs, 2009)

Novel Platforms for Oral Drug Delivery - P. Colombo; F. Sonvico; G. Colombo; R. Bettini (Pharmaceutical Research, 2009)

Validation of precipitation events in a regional climate model simulation using methods from complex systems theory - V. Pelino; A. Matera; T. Colombo; F. Giorgi (Theoretical and Applied Climatology, 2006)

CT—3D rotational angiography automatic registration: A sensitivity analysis - J. Stancanello; C. Cavedon; P. Francescon; P. Cerveri; G. Ferrigno; F. Causin; F. Colombo (Medical & Biological Engineering & Computing, 2005)

EU-OSTID: A Collection of Transposon Insertional Mutants for Functional Genomics in Rice - L. J. G van Enckevort; Gaëtan Droc; Pietro Piffanelli; Raffaella Greco; Cyril Gagneur; Christele Weber; Víctor M. González; Pere Cabot; Fabio Fornara; Stefano Berri; Berta Miro; Ping Lan; et al. (Plant Molecular Biology, 2005)

A Preliminary Trial Using Multi-target Polymerase Chain Reaction (multiplex PCR) and Restriction Fragment Length Polymorphism (PCR-RFLP) on the Same Feedstuffs to Detect Tissues of Animal Origin - F. Colombo; E. Marchisio; I.E. Trezzi; V. Peri; L. Pinotti; A. Baldi; G. Soncini (Veterinary Research Communications, 2004)

Transpositional behaviour of an Ac/Ds system for reverse genetics in rice - R. Greco; P. B. F. Ouwerkerk; R. J. de Kam; C. Sallaud; C. Favalli; L. Colombo; E. Guiderdoni; A. H. Meijer; J. H. C. Hoge†; A. Pereira (Theoretical and Applied Genetics, 2003)

Identification of Moulds Belonging to the Penicillium Genus using a Polymerase Chain Reaction (PCR-SSCP) Method Followed by 'Computer Assisted' Statistical Analysis of the Electrophoretic Patterns - F. Colombo; L. Vallone; R. Capoferri; I. Dragoni (Veterinary Research Communications, 2003)

Genomic changes in transgenic rice (Oryza sativa L.) plants produced by infecting calli with Agrobacterium tumefaciens - M. Labra; C. Savini; M. Bracale; N. Pelucchi; L. Colombo; M. Bardini; F. Sala (Plant Cell Reports, 2001)

Single-strand conformation polymorphism analysis of the glucose transporter gene GLUT1 in maturity-onset diabetes of the young - M. Baroni; F. Sentinelli; O. Massa; S. Romeo; C. Colombo; U. Di Mario; F. Barbetti (Journal of Molecular Medicine, 2001)

Effects of diet supplementation with carp ovary on gonad differentiation and growth of the European eel - G. Grandi; F. Poerio; G. Colombo; M. Chicca (Journal of Fish Biology, 2000)
Treating elvers of European eel Anguilla anguilla with mature carp ovary for 3–6 months during early growth induced female differentiation in 51·6–66·7% of treated animals compared with c . 5% in controls. The treatment also induced differentiation of ovaries in eels L T and a higher number of Syrski organs with ambisexual characters, and was most effective when administered at an early growth stage. The results could be attributed to the natural steroid content of the carp ovary. The total weight of treated animals at the end of the farm experiment was 84·7% higher than controls. The specific growth rate for weight was significantly higher in female yellow eels than in males, for both control and treated groups. The enhanced growth was related to induced feminization. A diet supplementation with mature carp ovary could be a good approach to control of sex differentiation and growth in eels.

Effect of drying methods on retention of moist sucralfate gel properties - L. Maggi; P. L. Catellani; E. Fisicaro; P. Santi; F. Zani; G. Massimo; P. Colombo (AAPS PharmSciTech, 2000)

Immunolocalization of the petunia floral binding proteins 7 and 11 during seed development in wild-type and expression mutants ofPetunia hybrida - P. E. Wittich; R. F. de Heer; X. -F. Cheng; H. Kieft; L. Colombo; G. C. Angenent; A. A. M. van Lammeren (Protoplasma, 1999)

1,2-Dichloropropane (DCP) toxicity is correlated with DCP-induced glutathione (GSH) depletion and is modulated by factors affecting intracellular GSH - R. Imberti; A. Mapelli; P. Colombo; P. Richelmi; F. Bertè; G. Bellomo (Archives of Toxicology, 1990)